Sustainability Learning: Project Based Learning Integrated Chemo-Entrepreneurship Approach to Understanding Chemistry and Interest in Entrepreneurship - Sitompul, Hamela Sari; Situmorang, Idawati; Tuty, Tuty (Jurnal Ilmiah Global Education, 2024)
This research aims to re-analyze how much influence the PjBL learning model integrated with the CEP approach has on students' learning outcomes and interest in entrepreneurship. This research used a pre-experimental design method through one group pretest - posttest design, which was carried out on 10 students in the first semester of the Agribusiness Study Program at Deli University, Sumatra. The data analysis instruments used were learning outcomes tests and questionnaires conducted before and after learning. The research results show that the N-gain is 0.84 with an increase in learning outcomes of 29.3%, this is because students can understand the material directly through project activities. In the interest in entrepreneurship which was tested through a questionnaire instrument, it was found that there had been an increase in the high category from 10.2% to 84.6% because through the integrated PjBL Model the CEP approach in the material studied was linked directly to entrepreneurial products, so that students became active and felt happy participating in activities. learning. Based on the results of research on the influence of implementing the PjBL Model integrated with the Chemo-Entrepreneurship (CEP) approach on students' understanding of chemistry and interest in entrepreneurship to determine the increase in learning outcomes in general chemistry lessons and students' entrepreneurial interest, it can be concluded that the application of the PjBL Model integrated with the CEP approach in chemistry learning can increasing students' understanding of chemistry and entrepreneurial interest.